2018
DOI: 10.1002/pra2.2018.14505501174
|View full text |Cite
|
Sign up to set email alerts
|

Fake it to make it, media literacy, and persuasive design: Using the functional triad as a tool for investigating persuasive elements in a fake news simulator

Abstract: How can we motivate social media users to critically analyze potential misinformation? Video games may be one way. This project presents research on a social‐impact game, Fake It to Make It, which positions players as for‐profit misinformation disseminators. Drawing upon the BJ Fogg's Functional Triad for Persuasive Computers and paying particular attention to the usability and perceived credibility of Fake It to Make It, this research analyzed the game from a persuasive design lens using player‐participant da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…A noteworthy approach is gamification (Basol et al, 2020, Roozenbeek and van der Linden, 2019, Katsaounidou et al, 2019, Urban et al, 2018. One example is a digital game that included the use of tools such as search engine search, reverse image research, image verification assistant and fact checkers (Katsaounidou et al, 2019).…”
Section: Proactive Training Of Specific Fake News Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A noteworthy approach is gamification (Basol et al, 2020, Roozenbeek and van der Linden, 2019, Katsaounidou et al, 2019, Urban et al, 2018. One example is a digital game that included the use of tools such as search engine search, reverse image research, image verification assistant and fact checkers (Katsaounidou et al, 2019).…”
Section: Proactive Training Of Specific Fake News Detection Methodsmentioning
confidence: 99%
“…Interestingly, across intervention and control group, there was a linkage between fake news detection skills and knowledge about the workings of news media, although the research design did not permit the closer examination of this relationship. In addition, some digital games touch on the broader dynamics through which disinformation is being shared, albeit to a very limited extent (Urban et al, 2018, Roozenbeek and van der Linden, 2019, Basol et al, 2020. It was, in fact, suggested that a way to improve one game would be to integrate more information about underlying political motives and dynamics (Urban et al, 2018).…”
Section: Development Of a Critical Understanding Of Media Systemsmentioning
confidence: 99%
“…We then manually searched the reference lists in these five studies and found another potentially eligible paper (Saleh et al, 2021). Finally, we searched Google with the following search query: "fake news game" and found three more potentially eligible studies (Grace & Hone, 2019;Micallef et al, 2021;Urban et al, 2019). However, after examining the titles, abstracts, and results of these four additional papers, we found that they did not meet our inclusion criteria.…”
Section: Aims Of the Present Papermentioning
confidence: 99%
“…Another strand of research has used gamified tools that have been developed primarily for the purpose of educating users about common misinformation tactics and characteristics. Specifically, games such as Fake It To Make It (Urban et al, 2018), Bad News (Roozenbeek & van der Linden, 2019), Harmony Square , Go Viral! (Basol et al, 2021), and Cranky Uncle (Cook et al, 2022) teach players common techniques for promoting misinformation in the hope that this has an inoculating effect (van der Linden et al, 2020).…”
Section: The (Mis)information Game: a Social Media Simulatormentioning
confidence: 99%